NO/RUNX3/kynurenine metabolic signaling enhances disease aggressiveness in pancreatic cancer. Issue 11 (19th November 2019) - Wang, Limin; Tang, Wei; Yang, Shouhui; He, Peijun; Wang, Jian; Gaedcke, Jochen; Ströbel, Philipp; Azizian, Azadeh; Ried, Thomas; Gaida, Matthias M.; Yfantis, Harris G.; Lee, Dong H.; et al.
Abstract : Pancreatic ductal adenocarcinoma (PDAC) is a lethal malignancy and is refractory to available treatments. Delineating the regulatory mechanisms of metabolic reprogramming, a key event in pancreatic cancer progression, may identify candidate targets with potential therapeutic significance. We hypothesized that inflammatory signaling pathways regulate metabolic adaptations in pancreatic cancer. Metabolic profiling of tumors from PDAC patients with a high‐ (>median, n = 31) and low‐NOS2 (inducible nitric oxide synthase; <median, n = 32) mRNA expression was performed. Differentially abundant metabolites were analyzed and linked with patient survival. The functional role of the prognostically significant metabolite and the mechanism of its regulation by NOS2/NO (nitric oxide)‐mediated signaling pathway was elucidated. The level of kynurenine, a tryptophan metabolite, was associated with high NOS2 expression, and a higher level of kynurenine predicted poor survival in patients ( n = 63, p = 0.01). Gene expression analysis in PDAC tumors ( n = 63) showed a positive correlation between the expression of NOS2 and the tryptophan/kynurenine pathway genes, including indoleamine‐2, 3‐dioxygenase 1 (IDO1) and several aryl hydrocarbon receptor (AHR)‐target genes including NFE2L2 ( NRF2 ), SERPINB2, IL1b, IL6 and IL8, which are implicated in pancreatic cancer. Consistently, treatment of pancreatic cancer cell lines with NO donor induced IDO1, kynurenine production and the expression of AHR‐target genes. Furthermore, kynurenine treatment enhanced spheroid growth and invasive potential of pancreatic cancer cell lines. Mechanistically, NO ‐induced IDO1/Kynurenine/AHR signaling was mediated by RUNX3 transcription factor. Our findings identified a novel NO /RUNX3/Kynurenine metabolic axis, which enhances disease aggressiveness in pancreatic cancer and may have potential translational significance in improving disease outcome. Abstract : What's new? Metabolic reprogramming is a key biological event supporting pancreatic cancer progression but the regulatory mechanisms of metabolic adaptations in the tumors are not well defined. Here the authors focused on inflammatory signaling pathways and performed metabolic profiling of tumors with high or low inducible nitric oxide synthetase expression. They define a new metabolic axis composed of nitric oxide, the transcription factor RUNX3 and the tryptophan metabolite kynurenine that correlates with disease aggressiveness and may be useful in designing novel therapeutic approaches to improve patient outcome.